Pengaruh Konten Tiktok dan Kepercayaan Terhadap Preferensi Pasien dalam Memilih dr. Arie Adrianus Polim, D. Mas, Sp. Og(K) - Johan, Rully; Lahindah, Laura (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the influence of Dr. Arie Adrianus Polim's presence as an Obgyn specialist on TikTok and trust simultaneously on patients' preferences in choosing an Obgyn. This type of study falls under quantitative research with a cross-sectional design. The population in this study involves all followers of Dr. Arie Adrianus Polim's TikTok account @dokAriePolim, amounting to 73,500 people. The sample size was calculated using Slovin's formula. The sample size is 100 respondents, using convenience sampling as the sampling method. Data collection techniques included questionnaires and literature studies. Hypothesis testing utilized simultaneous tests (F test) and t-test (partial), as well as multiple linear regression, along with the coefficient of determination (Adjusted R²). The results of the data analysis show that the regression model as a whole is not significant in predicting patient preferences (Y). Partially, (1) TikTok content (X1) has a regression coefficient ß= 0.073 (p = 0.202 > 0.05). Trust (X2) has a regression coefficient ß= 0.082 (p = 0.119 > 0.05), meaning that the influence of the TikTok content variable (X1) and Trust (X2) on Consumer Preferences (Y) in this study is not significant, with positive beta coefficients, indicating a unidirectional but insignificant effect. The predictive strength of the model is very weak, indicated by an R² value of 0.017. This means that only 1.7% of the variation in patient preferences is explained by TikTok content and trust, while 98.3% is influenced by other factors outside the model.